Study on the microstructure and comprehensive performance modification of SAC105-Co composite solder by magnetic field - Xing-yu Guo; Liang Zhang; Chuan-jiang Wu; Yu-hao Chen; Xin-quan Yu; Quan-Bin Lu; Xiang-jun Lu (Journal of Materials Research and Technology)
As a ferromagnetic transition metal, cobalt has been demonstrated to improve the mechanical properties and microstructural characteristics of Sn-1.0Ag-0.5Cu (SAC105) solder. Nevertheless, the underlying mechanisms of how external magnetic field affect the interfacial reaction behavior, intermetallic compound (IMC) formation, and mechanical performance of solder joints remain to be systematically investigated. This study investigated the IMC growth and microstructure evolution of SAC105-xCo (x = 0.02, 0.06, 0.1, 0.3, 0.4 wt%) solder in magnetic field. In addition, the wettability and shear strength of the solder joints were measured. The results revealed that the magnetic field application significantly refined the eutectic microstructure in the matrix at cobalt contents below 0.1 wt%. Owing to the grain refinement strengthening mechanism, both the shear strength and microhardness of the solder joints exhibited enhancement. Based on fracture morphology, it was determined that the fracture predominantly occurred within the solder matrix. However, at elevated content, Co particles tended to aggregate within the matrix, leading to the formation of (Cu, Co)6Sn5 IMC with irregular morphology. The fracture propagation exhibited a transition from the ductile solder matrix to the brittle IMC layer and the wettability of the solder was reduced. The study also found that in the magnetic field, adding Co caused stacking of grains in the interfacial layer, which increased the thickness of the IMC layer. However, in the SAC105–0.06Co/Cu solder joint, the IMC layer growth was inhibited.